Refractory congenital ascites as a manifestation of neonatal sialidosis: clinical, biochemical and morphological studies in a newborn Syrian male infant : presented in part at the 12th International Meeting of the German Pediatric Pathologists (Halle, Germany, 20th-22nd November, 1998) - Sergi, Consolato M.; Beedgen, Bernd; Kopitz, Jürgen; Zilow, Eugen; Zoubaa, Saida; Otto, Herwart F.; Cantz, Michael; Linderkamp, Otwin (American journal of perinatology, 1999)
A Syrian newborn with coarse facies, hepato-splenomegaly, and refractory ascites is reported. Examination of the ascitic fluid showed vacuolated lymphocytes and thin-layer chromatography of urinary oligosaccharides revealed an abnormal pattern indicative of sialidosis. Despite intensive care, the baby died of respiratory insufficiency 28 days after birth. In cultured skin fibroblasts an increase of the incorporation of [14C]methylamine pointed to excessive lysosomal storage and the demonstration of an isolated deficiency of alpha-N-acetylneuraminidase (sialidase) led to the diagnosis of a sialidosis. At postmortem examination, foam cells were found mostly in bone marrow, liver, and brain. To date very few cases of neonatal sialidosis have been reported, and, to the best of our knowledge, this is the first child with neonatal sialidosis from Syria and the first case of neonatal sialidosis studied by the [14C]methylamine incorporation assay.
Gesehen am 02.11.2017
Keywords: Konferenzschrift